1995
DOI: 10.1006/dbio.1995.1002
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of cDNAs for the Precursor Protein of a Low-Molecular-Weight Subunit of the Inner Layer of the Egg Envelope (Chorion) of the Fish Oryzias latipes

Abstract: cDNA clones for L-SF, the precursor of a low-molecular-weight subunit (ZI-3) of the inner layer of the Oryzias latipes egg envelope were isolated from Lambda ZAP cDNA libraries constructed from the poly(A)+ RNA of the liver of spawning female fish and estrogen-treated male fish. Among them, a clone, L-SF41, is 1473 bp long and contains an open reading frame encoding a signal peptide of 19 amino acids and L-SF protein of 420 amino acids. L-SF protein seems to be glycosylated, judging from the result of the glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 0 publications
2
68
0
Order By: Relevance
“…We detected the expression of all three AsZP3s in the testes of two 3-year-old male individuals (Fig. 5), while the earlier observations have found the liver of male fish can synthesize ZP proteins induced by estradiol (Murata et al 1995). So fish ZP3 genes may display a wide tissue distribution other than ovary and liver.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…We detected the expression of all three AsZP3s in the testes of two 3-year-old male individuals (Fig. 5), while the earlier observations have found the liver of male fish can synthesize ZP proteins induced by estradiol (Murata et al 1995). So fish ZP3 genes may display a wide tissue distribution other than ovary and liver.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, medaka (Murata et al 1995), rainbow trout (Hyllner et al 2001), and gilthead seabream (Del Giacco et al 1998) synthesized ZP3 protein in liver, which is in contrast to chickens, mice, Xenopus, crucian carp, goldfish, common carp, and zebrafish. In chickens, synthesis occurs in granulose cells (Waclawek et al 1998); whereas in mouse, Xenopus, and crucian carp, it occurs in the oocyte (Fan et al 2001;Yamaguchi et al 1989;Waclawek et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, ZP3 is also synthesized in the growing oocytes and constitutes the egg envelope from the inside of the oocytes [4]. In contrast with crucian carp and mammals, however, ZP3 of another fish medaka ( Oryzias latipes) is synthesized only in liver but not in ovary of spawning female fish [38]. As shown by Waclawek et al, the chicken ZP3 is expressed exclusively in the granulosa cells surrounding oocytes [39].…”
Section: Discussionmentioning
confidence: 99%
“…A search of GeneBank database revealed that the ZP3 amino acid sequences of gyno-and gonocarp were homologous to that of the egg envelope glycoprotein ZP3 isolated from common carp [33], zebrafish [37], medake [38], Xenopus [31] and chicken [39], [40] and of mammalian zona pellucida ZP3 isolated from mouse [41] and human [42]. The level of sequence identity was found to be highly significant among a variety of fish species.…”
Section: Homology Among Fish Zp3 Proteins and Other Vertebrate Zp Promentioning
confidence: 99%